Language and Gender Use of Linguistic Forms in Your Place or Mine Movie 2023 - Maulidya, Mutia; Arvian, Elsan; Setiawan, Wawan (Sekolah Tinggi Bahasa Asing JIA, 2024)
This study aims to find out the differences in the forms of linguistic behavior and linguistic functions between male and female language and in the film Your Place or Mine. This study combines Robin Lakoff's theory to analyze ten types of female language and Jenifer Coates' theory to analyze four types of male language. Then, Janet Holmes' theory to classify linguistic behavior. This research uses a qualitative descriptive method. Meanwhile, data were collected through observation and in - depth observation of the use of linguistic forms and behaviors by categorizing tag questions, lexical hedges, raising intonation, avoiding strong swear words, super polite forms, emphatic stress, hypercorrect grammar, intensifiers and empty adjectives, minimal response, command and directive, topic choice and swear words. It found 55 data divided into 13 categories of linguistic forms, namely 4 linguistic forms of female language and 9 linguistic forms of male language. Based on the differences in linguistic behavior and topics, women use tag questions more often than men. In addition, intonation is also different due to the difference in role status between men and women.